Mangafodipir-DPDP enhanced MRI visualization of a pancreatic adenocarcinoma previously undetected by extracellular contrast anhanced CT and MRI - De Filippo, M.; Bocchi, C.; Quartieri, et al., L. (Acta Biomedica Atenei Parmensis, 2007)
We report a case of adenocarcinoma of the head of the pancreas, occult at extracellular contrast enhanced MDCT and magnetic resonance imaging (MRI), which was detected by MRI only with the use of a tissue-specific contrast agent (Mangafodipir trisodium Mn- DPDP). The histological examination after duodenopancreatectomy confirmed the diagnosis. Contrast-enhanced multi-detector computed tomography (MDCT) is currently considered to be the reference method for diagnosing and staging of pancreatic adenocarcinoma. Endoscopic Ultrasounds (EUS) with fine needle aspiration (FNA) is an accurate but invasive procedure. The technological evolution of magnetic resonance imaging and the development of organ-specific contrast media for liver and pancreas have led to a progressively more extensive use of this method for the investigation of suspected lesions. Moreover, this technique is particularly useful when MDCT gives unclear or debatable diagnostic responses.